2000
DOI: 10.1046/j.1469-7580.2000.19610085.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the anatomy of the epineurium of the canine recurrent laryngeal nerve

Abstract: The purpose of this investigation was to determine the amount of epineurium surrounding the recurrent laryngeal nerve (RLN) compared with a limb nerve, that to flexor hallicus longus (NFHL). Nerve samples were obtained from 10 adult dogs and studied using scanning electron microscopy and light microscopy to measure the relative proportion of epineurium and the relative proportions of adipose and collagenous tissue comprising the epineurium in both nerves. Significantly greater relative epineurial cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
3
15
0
1
Order By: Relevance
“…4 This study demonstrated a significant difference in the amount and makeup of the epineurium in the left RLN compared to the NFHL. The RLN exhibited a significantly greater amount of adipose tissue and relative cross-sectional area consisting of epineurium than the NFHL nerve.…”
Section: Introductionmentioning
confidence: 57%
“…4 This study demonstrated a significant difference in the amount and makeup of the epineurium in the left RLN compared to the NFHL. The RLN exhibited a significantly greater amount of adipose tissue and relative cross-sectional area consisting of epineurium than the NFHL nerve.…”
Section: Introductionmentioning
confidence: 57%
“…Extra padding surrounding the RLN could help to prevent damage resulting from, for example, blows to the neck, compression and elongation related to movements of the head, such as flexion, extension, and rotational movements, and the elevation and depression that occur during swallowing and voice production. 16 Journal of Voice, Vol. 25, No.…”
Section: Discussionmentioning
confidence: 99%
“…The factors protecting the peripheral nerves against stretching can be attributed to their anatomical structure and biomechanical characteristics (Barkmeier and Luschei, 2000;Phillips et al, 2004;Topp and Boyd, 2006;Vivo et al, 2004). The structural organization of peripheral nerves enables them to function while resisting and adapting to stresses placed on them by varying postures and movements.…”
Section: Introductionmentioning
confidence: 99%